Effect of Nebulization With 3% Hypertonic Saline for Airway Clearance on Mechanically Ventilated Patients Admitted in ICUs of Pt. B.D. Sharma, PGIMS, Rohtak - Pratibha Rani Nanda; Rajpati Amrawat; Shaveta (International Journal of Emergency and Trauma Nursing and Practices, 2023)
Background of the Study: The ability to breathe artificially prolongs life in many situations. Patients requiring mechanical breathing in the intensive care unit are more likely to have complications and even death due to a variety of interconnected causes. As a result, it became critical to rapidly ventilate in the safest and most efficient manner available. Intubated patients have benefited from nebulized suctioning, as it improves lung clearance and decreases the risk of infection. Objectives: To evaluate the effect of nebulization with 3% hypertonic saline for airway clearance on mechanically ventilated patients admitted to ICUs by Pt. B. D. Sharma, PGIMS, Rohtak. Methodology: For this study, a quasi-experimental research design was selected, and the samples for the study were selected from the ICUs of PGIMS Rohtak, Haryana. Samples were chosen using a convenience sampling approach, with a total sample size of 40. Data collection was done with the structured tool, which consisted of socio-demographic variables, clinical variables, and bio-physiological parameters. The collected data was subjected to analysis utilizing both descriptive and inferential statistical methods. Results: During the pre-test, among the samples in the experimental group, the post-test mean and standard deviation were 3.40±2.30. The control group exhibited a post-test mean and standard deviation score of 10.50±2.60, with a mean difference score of 7.1. The independent 't' test value, computed with degrees of freedom, was –9.130. This reached statistical significance at a p value of <.005. Conclusion: Maintaining airway patency in mechanically ventilated patients using hypertonic saline nebulization has been demonstrated to be a straightforward, low-cost, and successful therapy method.
Keywords: Hypertonic saline nebulized suctioning; airway clearance; mechanical ventilation